13-顺式维甲酸联合IFN-α-2b治疗套细胞淋巴瘤的动物实验研究 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To determine the anti-tumor effects of 13-cis-retinoic acid (13cRA) combined with interferonα-2b (IFNα-2b) in mantle cell lymphoma (MCL) animal model. METHODS: The animal model of MCL was established by introducing Jeko-1 cell line into severe combined immunodeficiency disease mice. The successfully tumor-developed mice were assigned to different groups treated with negative control group (solvents), 13cRA (high dose: 200mg/kg; middle dose: 100mg/kg; low dose: 50 mg/kg) alone, IFNα-2b alone or combination of different dose of 13cRA with IFNα-2b, and positive control group (bortezomib, rituximab, cyclophosphamide), respectively. Variations of tumor volume were observed regularly. The relative tumor proliferation rate and tumor inhibition rate were calculated. Immunohistochemistry stain was used to detect the Ki-67 expression and TUNEL was applied to measure the apoptosis of tumor cells. Furthermore, the levels of Cyclin D1, caspase 9 and Rb protein were measured by Western-blot method. RESULTS: ①The relative tumor proliferation rates (T/C%)were 30%, 37%, 32% and 33% in middle dose, high dose groups of 13cRA as well as their combination with IFN α-2b, respectively. ②Comparing with the negative control, both 13cRA at different doses and its combination with IFNα-2b remarkably inhibited the tumor growth (P<0.05), while no statistic significance existed in different dose group of 13cRA. IFN-α 2b alone didn't demonstrate the tumor-inhibition effects (P>0.05). Middle dose of 13cRA and its combination with IFN-α-2b demonstrated relatively high tumor-inhibition effects (59.2% and 62.6% respectively), which were similar to the effects in positive control (69.4%). ③There was no statistic difference of Ki-67 in each experimental group. ④Comparing with negative control group, all doses of 13cRA and their combinations with IFNα-2b remarkably increased the apoptosis (P<0.05), similar to the positive control group (P>0.05). However, IFNα-2b alone didn't promote the apoptosis of tumor tissue (P=0.098). ⑤Comparing with negative control group, IFNα-2b combined with each dose of 13cRA significantly decreased the levels of cycling D1 and procaspase-9, while increased the level of cleaved caspase-9 (P<0.05), which were similar to the positive control group (P>0.05). Nevertheless, 13cRA alone didn't demonstrate such effects. CONCLUSION: In the MCL animal model, IFNα-2b alone showed no effects, but combined with IFNα-2b, 13cRA displayed anti-tumor effects at different doses. The anti-tumor mechanism of 13cRA combined with IFNα-2b was probably down-regulation of the cyclin D1 expression, inhibition of cell proliferation and induction of apoptosis by activating caspase-9.